Budd-Chiari Syndrome: Pathogenetic Factors and Completeness of Screening for Paroxysmal Nocturnal Hemoglobinuria - Mandala, Aashray; Bravo-Perez, Carlos; Brady, Zachary; D'Addona, Matteo; Durmaz, Arda; Orland, Mark; Lakhotiya, Kartik; Haddad, Christopher; Thiagarajan, Praveena; Visconte, Valeria; Gurnari, Carmelo; Maciejewski, Jaroslaw (Blood, 2024)
Among thrombosis occurring in unusual anatomical sites, the hepatic circulation, namely Budd-Chiari syndrome (BCS), represents one of the rarest localizations, with an incidence rate of 2 cases per million. BCS is characterized by a diverse pathophysiology with several associated disorders, including myeloproliferative neoplasm (MPN), malignancies, and various hypercoagulable states. While JAK2 MN are now a well-recognized culprit, paroxysmal nocturnal hemoglobinuria (PNH) may be less recognized. Nevertheless, the true proportion of BCS that can be attributed to each underlying condition is not fully characterized. We conducted our study on completeness of clinical workup regarding the exclusion of PNH as causative trigger. For comparison we also used the screening and detection for JAK2 mutations. From the viewpoint of PNH, appropriate screening may lead to identification of cryptic cases of particular importance now that effective treatment for thrombophilia due to PNH is available. We determined the etiologic fraction of thrombophilic disorders in particular PNH leading to BCS by leveraging a large scale biomedical institutional database and the All of Us Research Program (N=410,235) used for comparative and validation purposes. Clinical information was queried to identify conditions known to cause hypercoagulable states, including factor V Leiden (FVL), prothrombin G20210A, JAK2V617F, UBA1 hotspots, protein C deficiency (PCD), Protein S deficiency (PSD), and antithrombin III (ATIII) deficiency. When available, laboratory values were checked to validate the above diagnoses. In the All of Us database, 134 subjects were reported with the diagnosis of BCS (32.66 per 100,000). Of these, M/F ratio was 0.49, with 17% of them (n=23) aged 18-44, 42% (n=56) aged 45-64, and 41% (n=55) aged >65 yrs. With regards to ethnicity, 52% were Caucasian, 23% were African American, while the rest were of other ethnicities. Overall, the JAK2V617F explained the highest proportion of BCS (6%), followed by FVL and antiphospholipid syndrome (APS), each found in 4.5% of the cases. Both ATIII and PSD were found at 1.5%, while only 0.75% had PCD. None of the BCS carried canonical UBA1 or had PNH as asserted by ICD coding derived from diagnostic workup. Conversely, less than 20 cases of PNH were reported but none of them, perhaps due to the granularity of clinical annotation, had coinciding BCS. Overall, the etiologic fraction of thrombophilic disorders leading to BCS in the All of Us database was found to be 20%. A parallel analysis was performed in the institutional database of a tertiary academic center with a integrated hospital and family health center networks. After excluding pediatric (<18 yrs) patients to match the inclusion criteria of the All of Us, 1,124 BCS cases were found (10.7 per 100,000 patients). Within this cohort, M/F ratio was 0.73, with 26% (n=294) of patients aged 18-44, 41% (n=458) between 45-64, and 33% (n=372) 65 yrs or above. In terms of ethnicity, 76% (n=872) were Caucasian, 15% (n=163) were Black, and 1% were Asian (n=15). The most common thrombophilic condition was found to be APS (2.6%, n=29). FVL was also frequent, with 2.2% (n=25) of patients carrying the condition. Both PCD and PSD were present in 0.5% of the cohort (n=6), whereas only 1 patient (0.1%) was found to have Prothrombin G20210A. The JAK2V617F was found in 27 patients. However, JAK2V617F was screened for only 11% of cases, resulting in a positivity rate of JAK2 testing in BCS of 21%. Comparatively, a coinciding diagnosis of PNH was present in 1.25% (n=15) of BCS. However, the more suitable denominator would be the number of BCS who were screened. Of the 1,124 patients with BCS, PNH screening was performed in 7.2% of patients, estimating the true incidence of PNH within BCS of 18.5%. Of the 15 BCS-PNH patients, 20% were between 18-44 yrs old, 40% were between 45-64 yrs old, and 40% were aged >65 yrs. Additionally, M/F ratio was 0.67. Finally, in terms of ethnicity, 69% of the cohort was Caucasian, 27% were Black, and 1% were Asian. Overall, the etiologic fraction of explored thrombophilic disorders was found to be 9.6%. To sum up, PNH screening is currently incomplete in BCS, but, if performed, we estimate it is close to 20% of patients afflicted with BCS will have co-associated PNH diagnosis, indicating the importance of thorough testing for PNH in BCS. We thank the NIH All of Us Research Program No relevant conflicts of interest to declare.